1999
DOI: 10.1128/iai.67.5.2452-2463.1999
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Immune Responses toNeisseria meningitidisin Children

Abstract: There is an urgent need for effective vaccines against serogroup B Neisseria meningitidis. Current experimental vaccines based on the outer membrane proteins (OMPs) of this organism provide a measure of protection in older children but have been ineffective in infants. We postulated that the inability of OMP vaccines to protect infants might be due to age-dependent defects in cellular immunity. We measured proliferation and in vitro production of gamma interferon (IFN-␥), tumor necrosis factor alpha, and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 62 publications
0
14
1
1
Order By: Relevance
“…Different trials have shown that meningococcal vaccines constituted by OMV are efficient for adults and children older than 2 years of age, but not for infants (16,18). One reason for the failure of the vaccine in young children seems to be the difference in some cytokine production profiles in young children (20). Furthermore, there is also a difference in the quality of the antibodies in young children, since the serum bactericidal activity of IgG is also low (20).…”
Section: Discussionmentioning
confidence: 99%
“…Different trials have shown that meningococcal vaccines constituted by OMV are efficient for adults and children older than 2 years of age, but not for infants (16,18). One reason for the failure of the vaccine in young children seems to be the difference in some cytokine production profiles in young children (20). Furthermore, there is also a difference in the quality of the antibodies in young children, since the serum bactericidal activity of IgG is also low (20).…”
Section: Discussionmentioning
confidence: 99%
“…Genetically determined high IL-10 production has been shown to be a risk factor for fatal outcome of meningococcal disease (Westendorp et al, 1997). Furthermore, it has been shown, that meningococcal infection in young children leads to a low IL-10/IFN-gamma ratio whereas in older children the IL-10/IFN-gamma ratio tends to be higher (Pollard et al, 1999). The reason for low IL-10 levels induced by encapsulated meningococci is the antiphagocytotic property of the capsule.…”
Section: Discussionmentioning
confidence: 99%
“…Outer membrane vesicles from MenB were kindly prepared by Dr Jamie Findlow and Dr Ray Borrow, Vaccine Evaluation Unit, Health Protection Agency Northwest (Cartwright et al, 1999;Pollard et al, 1999). OMV were derived from the Norwegian clinical invasive strain H44/76 (B:15:P1.7,16) and the isogenic mutants TR4 (B15:P1.7-8,4) and TR10 (B:15:P1.5-2,10) (Cartwright et al, 1999;Pollard et al, 1999). These differ only in the major outer membrane protein Porin A, and have been selected to be representative of likely colonizing strains in the UK.…”
Section: Control and Meningococcal Antigensmentioning
confidence: 99%